Penegakan Hukum Tindak Pidana Pencemaran Nama Baik Melalui Media Sosial Di Indonesia - Abustam, Abustam (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2021)
The purpose of this research is to know How the regulation of Criminal Act through social media and The Law Enforcement of Defamation through social media in the Directorate of Special Criminal Investigation Polda NTB. The type of research is using the normative and empirical. The approaches of this research are used legislation, conceptual and sociological. The Material Law are used primary and secondary. Data analysis is used qualitative analysis. The process of implementation of law enforcement is as same as the Criminal Procedure Code but through verification that proven through electronic document in the form of print out result of screenshot from Facebook social networking web site which containing defamation statement.